Pengaruh Disiplin Kerja, Motivasi, Budaya Organisasi Dan Stres Kerja Terhadap Kepuasan Kerja Guru Pada Slta Di Bawah Yayasan Muhammadiyah Se Kabupaten Purworejo - Caryono, Suhas (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
This thesis aims to determine the effect of work discipline, motivation, organizational culture, and work stress on teacher’s job satisfaction at the high school under the Yayasan Muhammadiyah Purworejo District. The research results showed that there are positive effects of variable work discipline of teacher’s job satisfaction evidenced by the regression coefficient of 0.156 with p value = 0.024 0.05, positive influence motivational variables of teacher’s job satisfaction evidenced by the regression coefficient of 0.218 with p value = 0.018 0.05, positive influence on organizational culture variables job satisfaction of teachers demonstrated the regression coefficient of 0.472 with p value = 0.000 0.05, negative effect of work stress variables on teachers' job satisfaction evidenced by the regression coefficient of - 0.233 with p value = 0.000 0.05 and positive influence of work discipline, motivation, and organizational culture stress work simultaneously on teacher’s job satisfaction evidenced by the regression coefficient value of 42.367 with p value = 0.000 0.05 with an influence of 62.60%.